Advanced Renal Pelvic Carcinoma Revealed after Treatment of a Staghorn Calculus by Endoscopic Combined Intrarenal Surgery. (30th May 2020) - Tsuboi, Ichiro; Maruyama, Yuki; Araki, Motoo; Ando, Nobuyoshi; Nishiyama, Yasuhiro; Arata, Ryoji; Ono, Noriaki
Abstract : Renal pelvis carcinoma associated with staghorn calculus is a clinically rare condition. A 66-year-old man presented with flank pain due to an 8 cm complete staghorn calculus. We performed three lithotomies using endoscopic combined intrarenal surgery and carried out intraoperative biopsy. Histopathological examinations revealed a keratinized lesion. One month later, contrast-enhanced computed tomography showed an advanced renal pelvis carcinoma. These findings demonstrate that even an intraoperative biopsy may be insufficient to diagnose a renal pelvis carcinoma associated with a staghorn calculus. The possibility of RPCa developing when treating a long-standing staghorn calculus should therefore be kept in mind.